Quantitative Comparison and Chemical Profile of Different Botanical Parts of Panax notoginseng From Different Regions - Gao, Mengyuan; Cao, Xiunan; Wei, Shujie; Huang, Xuhua; Ouyang, Huizi; Chang, Yanxu; Shi, Rui; He, Jun (Frontiers in Nutrition, 2022)
The root of Panax notoginseng, a highly valued medicine and functional food, is the main part used for medicinal purposes. However, the stems and leaves are also used in practice. To provide a chemical basis for various uses, a quantitative comparison of eighteen saponins using a non-targeted metabolomics approach was established, so as to investigate the chemical profiles of the different parts of P. notoginseng. The established strategy revealed that roots and stems, with their similar chemical characteristics, consisted mainly of protopanaxatriol-type saponins, whereas protopanaxadiol-type saponins were principally present in the leaves. Multivariate analysis further suggested that the quality of the stems and leaves of P. notoginseng was significantly affected by its geographical origin. Furthermore, 52 constituents (26 non-volatile and 26 volatile) were identified as potential markers for discriminating between different parts of the plant. Taken together, the study provides comprehensive chemical evidence for the rational application and exploitation of different parts of P. notoginseng.